Eocene-Oligocene paleoceanography of the subantarctic South Atlantic: Calcareous Nannofossil reconstructions of temperature, nutrient, and dissolution history - Pea, Laura (Università degli Studi di Parma. Dipartimento di Scienze della Terra, 2011)
Extremely warm 'Greenhouse' climates of the early Eocene came to a gradual end during a prolonged interval of global climatic deterioration in the middle-to-late Eocene (~49 to 34 Ma), resulting in the eventual initiation of an 'Icehouse' climate state in the early Oligocene. This global climatic transition represents one of the most significant climate changes of the Cenozoic and is punctuated both by prominent cooling steps and by several transient warming and cooling phases superimposed on the long-term cooling trend. This dissertation focuses on two key periods of accelerated climatic change during this interval: the Middle Eocene Climatic Optimum (MECO) (~40 Ma) and the Eocene-Oligocene Transition (EOT) (~34 Ma). The MECO is a transient (500 kyr) warming event recorded worldwide by foraminiferal oxygen isotopes and is associated with deep-ocean acidification. In contrast, the EOT is associated with expansion of Antarctic ice sheets, global cooling, sea level fall, marine and terrestrial biotic turnover, and deepening of the calcite compensation depth (CCD). Calcareous nannofossil assemblages are used to investigate both surface-water environments and deep-sea dissolution across these events at drill sites in the South Atlantic Ocean. Paleoecological study of the nannofossil assemblages is employed to reconstruct temperature and nutrient changes at the sea surface, and analysis of preservation state of individual nannofossil taxa is used to constrain the history of CCD fluctuations. In Chapter 2, the MECO interval was studied at Ocean Drilling Program (ODP) Site 702 (50°S; Islas Orcadas Rise) using quantitative analysis of calcareous nannofossil assemblages in the time interval between 43.5 and 39.5 Ma. Biostratigraphic analysis shows that the MECO event corresponds to significant nannofossil turnover, with five biostratigraphic events occurring in conjunction with warming. Paleoecological interpretation of the assemblages also indicate that temperature and nutrient conditions of surface waters at this site ...